Final answer:
To write G(jω) in the form G(jω) = u(ω) + jv(ω), we substitute jω for s in the given transfer function, G(s). By simplifying the expression step by step, we find that u(ω) = -ω³ + 12 and v(ω) = (15ω² + 10ω) / (jω + 1).
Step-by-step explanation:
To write G(jω) in the form G(jω) = u(ω) + jv(ω), we substitute jω for s in the given transfer function, G(s).
Let's simplify the expression G(jω) step by step:
- (jω + 3)((jω)² + 2(jω) + 4) / ((jω) + 1)
- (jω + 3)(-ω² + 2jω + 4) / (jω + 1)
- (-ω³ + 3jω² + 4jω + 12ω² + 6jω + 12) / (jω + 1)
- (-ω³ + 15jω² + 10jω + 12) / (jω + 1)
- (-ω³ + 12) + (15jω² + 10jω) / (jω + 1)
Therefore, u(ω) = -ω³ + 12 and v(ω) = (15ω² + 10ω) / (jω + 1).